A guide to sustainability analysis organisations (Paris, 2001)
"In recent years, the capital markets have seen the arrival of a number of funds and market indices said to be ethical, socially responsible, or friendly to sustainable development. Today, the volume of assets invested according to ethical criteria totals more than € 1500 billion worldwide."